Исследование влияния гендерного развития наформирование социальной активности детей с нарушениями зрения - Маллаев, Дж. М.
The article presents the results of invest igations of the infl uence of gender on the formation of social development activities of children 5-6 and 7-8 years visually impaired.
Keywords: Дошкольный возраст; Патология зрения